Methods for estimating the maximal lactate steady state in trained cyclists - Harnish, C. R.; Swensen, T. C.; Pate, R. R. (Medicine & Science in Sports & Exercise, 2001)
Purpose: Maximal lactate steady state (MLSS) is the highest exercise intensity at which blood lactate concentration (HLa) remains stable. In this study, we examined the validity of simulated 5-km and 40-km time trials (TT) as methods for estimating average speed at MLSS in cyclists. Methods: Nine trained cyclists reported to the laboratory for five to seven exercise trials. Testing included a VO2max test, a simulated 5-km and 40-km TT, and several 30-min MLSS trials. Results: Mean VO2peak was 4.42 +/- 0.13 L.min-1, whereas VO2 at MLSS (N = 8) was 3.54 +/- 0.15 L.min-1, representing 80.1 +/- 4.1% of VO2peak. HR and HLa at MLSS were 174.7 +/- 2.6 b.min-1 and 6.9 +/- 0.8 mM, respectively. MLSS speed was 36.8 +/- 1.0 km.h-1, which corresponded to 92.1 +/- 1.2% of 5 km average speed (AVS5km). Mean AVS, HLa, and HR during the 40-km TT were 36.6 +/- 0.9 km.h-1, 6.3 +/- 0.7 mM, and 174.1 +/- 2.1 b.min-1, respectively, and did not differ from those at MLSS. Conclusions: Both the (simulated) 5-km and 40-km TT can be used to estimate the MLSS in cyclists. In addition, HLa at MLSS shows a large degree of variation between riders.